KEPUASAN KERJA KARYAWAN FOOD AND BEVERAGE SERVICE DEPARTMENT DI HOTEL GRAND TJOKRO PEKANBARU - Lestari, Delia Putri; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this research is how employee satisfaction Food and Beverage Service Department in work and how efforts to improve employee job satisfaction Food and Beverage Service Department in Grand Tjokro Hotel.This research was used descriptive quantitatif method to describe the issues. The sample used in this research was 7 people. Quesionnaires, interviews, and observations were used to collect the research data.The results of this research indicate that based on the research results obtained on the employee job satisfaction Food and Beverage Service Department at Grand Tjokro Hotel Pekanbaru quite satisfied. This is evidenced by the acquisition of the overall total score, which is 264 points. Challenging work mentally, appreciations, good work condition and colleagues who support are important things in improving the employees Food and Beverage Service Department work satisfaction.Keywords: Work satisfaction, employee Food and Beverage Service Department